Entrepreneurship education in German speaking Europe: a mapping - Ann-Kristin Achleitner; Christoph Kaserer; Svenja Jarchow; Karen Wilson (Technische Universität München, Center for Entrepreneurial and Financial Studies (CEFS), 2007)
Entrepreneurship education plays a crucial role in shaping the attitudes of students towards entrepreneurship as well as spurring the creation of future young companies. It is a crucial topic in any economy and increasingly becoming key on the agenda for universities around the world. In this study, we took a look at the higher education entrepreneurship education landscape in German-speaking Europe. We have reviewed all universities, including the technical ones, across Germany, Austria, Liechtenstein and German-speaking Switzerland, using a broad definition of entrepreneurship. Our goal was to capture information about all entrepreneurship related activities, not just those labelled 'entrepreneurship'. In this first phase of the work, we have focused on the entrepreneurship and related chairs, which are key hubs for providing teaching, generating research, launching activities and raising awareness.
Keywords: 330; Entrepreneurship; Entrepreneurship Education; Betriebswirtschaftsstudium; Unternehmensgründung; Studienfach; Benchmarking; Deutschland; Österreich; Schweiz